Fintech's Mediating Role in Financial Efficacy, Risk, and Investment Decisions - Anfas Anfas; Fajar Rakasiwi Syamsuddin (Studi Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the mediating role of financial technology (fintech) in the relationship between financial efficacy, risk perception, and investment decisions among Indonesian millennials in the capital market. Methodology: A quantitative approach was employed, utilizing an online questionnaire distributed to millennial investors in Indonesia. The collected data were analyzed using multiple linear regression analysis with SPSS to test both direct effects and mediating relationships. Findings: The results indicate that financial efficacy positively influences investment decisions, while risk perception exerts a significant negative effect. Fintech significantly mediates the relationships between both financial efficacy and investment decisions, and between risk perception and investment decisions. The complete model explains 56.8% of the variance in investment decisions. Conclusion: The study concludes that fintech platforms serve as a crucial mechanism through which financial efficacy and risk perception influence millennial investment behavior. Enhancing fintech features can effectively channel financial confidence while mitigating risk apprehensions, ultimately promoting capital market participation among younger investors. Limitations: The study's limitations include a relatively small sample size and the use of purposive sampling, which may affect the generalizability of the findings to the broader population of millennial investors. Contribution: Theoretically, this research extends Self-Efficacy Theory by validating fintech's mediating role in investment behavior. Practically, it suggests that securities companies and fintech developers should enhance user-friendly interfaces, educational features, and platform transparency to boost investor confidence and facilitate informed decision-making.